(untitled) (Jurnal Agroekoteknologi dan Agribisnis, 2022)
Tea is one of the most popular drinks. Frequently, tea is made from real tea leaves. However, apart from real tea leaves, tea can also be made from other materials, such as from dayak onion bulbs. Dayak onion tea provides health benefits because it has several chemical compounds such as alkaloids, glycosides, flavonoids, phenolics, steroids, triterpenoids, and tanins. The purpose of this study was to determine the effect of temperature and time on roasting onion dayak tea. The method used in this research was two-factor factorial experimental design. The first factor wasthe oven temperature of 130, 140, and 150 °C, respectively. The second factor is the oven time which duration of 20 minutes, 25 minutes, 30 minutes respectively and repeated 3 times. The variables observed were taste, aroma, and color using ANOVA analysis of variance, DMRT test, and Bayes method. The results showed that the taste level was dominated by the A2M3 treatment, the aroma level was dominated by two treatments, namely A2M3 and A3M3, the color level was dominated by the A1M3 treatment. The final result of three parameters measuring taste, aroma, and color obtained the best treatment namely A2M3 treatment with a value of 18,17 with oven temperature and time of 140 °C and 30 minutes. Flavonoid analysis might be needed in the future.